Sense of Religion : The Lifelong Religious Practice of the Evacuee Karelian Orthodox Women in Finland - Kupari, Helena (2015)
This study examines the lived religion of elderly Finnish Orthodox Christian women in present-day Finland. It discusses the women s everyday religious practice within the domestic environment. Furthermore, it also traces the ways in which their religion had been affected by their life histories, the changing status of the Orthodox community, and the modernization of Finnish society in the course of the 20th century. The primary research material for this study consists of interviews of 24 women. Finland is a Lutheran-dominated country; today, about one percent of Finns belong to the Orthodox Church. Traditionally, most of the Orthodox resided in Finnish Karelia. After the Second World War, Finland had to cede large areas of Karelia to the Soviet Union. In the process, two thirds of the Finnish Orthodox lost their homelands. All the interviewees, or their parents, had been among the evacuees from Karelia. The theoretical-methodological approach made use of in the study is based on practice theory. In particular, the concept of habitus as developed by the sociologist Pierre Bourdieu is applied to analyze the women s interview accounts. The concept captures Bourdieu s understanding of the reciprocal dynamic between practice, subjectivity, and structures of power. The analysis demonstrates that the interviewees religion was characterized by a movement between routine and reflexive action. Judging from the material, they mostly did religion in a habitual fashion. Nevertheless, they could also perform their practices more intentionally, to reinforce their identity against specific others. These two aspects of the women s religion are traced, respectively, to their childhood religious socialization and their social trajectories as minority religious practitioners in Finnish society. Ultimately, the analysis forms an account of the women s religion as habitus. The informants religious habitus constituted an embodied and practical sense of religion, which informed both their routine religious practices and more conscious ...